Динаміка клітинного складу лімфоїдних вузликів легень овальбумін-сенсибілізованих морських свинок - Попко, Світлана Сергіївна; Popko, S. S. (My University, 2022)
У статті розглянуто морфологічні аспекти динаміки клітинного складу лімфоїдних вузликів легень морських свинок як наслідок експериментального овальбумін-індукованого алергічного процесу. Вивчалася реактивність імунокомпетентних клітин лімфоїдних утворень легень після триразової підшкірної сенсибілізації та подальшої 8-денної інтраназальної аероалергізації овальбуміном у ранньому та пізньому періоді алергічного запального процесу мікроскопічним, морфометричним та статистичним методами. Застосування морфометричного аналізу дозволило виявити загальну закономірність реактивності місцевої специфічної ланки імунної системи легень на дію алергену, яка полягає в збільшенні середньої кількості імунокомпетентних клітин лімфоїдних вузликів легень, починаючи з 30-ї до 44-ї доби після початку експерименту. Серед усіх видів імунокомпетентних клітин лімфоїдних вузликів легень під час експерименту максимальний коефіцієнт збільшення в 5,8 раза спостерігався при підрахунку плазмоцитів. Статистично доведено, що реалізація овальбумін-індукованого алергічного запального процесу в легенях відбувається за гуморальним типом і тривалість його перебігу не обмежується безпосереднім впливом алергену, але й продовжується після закінчення його дії, що є проявом змін компенсаторно-пристосувальних процесів локальної імунної системи легень протягом овальбумін-індукованого алергічного запального процесу. The article discusses the morphological aspects of the dynamics of the cellular composition of lymphoid nodules in the lungs of guinea pigs as a result of an experimental ovalbumin-induced allergic process. We studied the reactivity of immunocompetent cells of lymphoid formations of the lungs after three times subcutaneous sensitization and subsequent 8-day intranasal aeroallergization with ovalbumin in the early and late stage period of the allergic inflammatory process by microscopic, morphometric and statistical methods. By help of morphometric analysis we demonstrate the general regularity of reactivity of a local specific link of the pulmonary immune system to the action of an allergen, which consists in the elevation of the average amount of immune cells of lymphoid nodules of the lungs, starting from the 30th to the 44th day after the start of the experiment. The maximal coefficient of increase by 5.8 times was observed in counting plasma cells among all types of immunocompetent cells of lymphoid nodules in the lungs during the experiment. It has been statistically proven that the implementation of the ovalbumin-induced allergic inflammatory process in the lungs proceeds according to the humoral type and the duration of its course is not limited by the direct influence of the allergen, it also continues after the end of its action, which is a manifestation of changes in compensatoryadaptive processes in the pulmonary immune system with ovalbumin-induced allergic inflammation.
Dynamics of the cellular composition of lymphoid nodules in the lungs of guinea pigs sensitized with ovalbumin.
Keywords: лімфоїдний вузлик; морська свинка; легеня; алергічне запалення; овальбумін; lymphoid nodule; guinea pig; lung; allergic inflammation; ovalbumin